Analisis Penerapan Akuntansi Manajemen untuk Mendukung Pertumbuhan dan Keberlanjutan UMKM - Rahman, Fadali; Purwanto, M. Adi; Rahayu, Runik Puji; Fitrianti, Rani Nur; Djaja, Mohammad Herman; Rohmaniyah, Rohmaniyah; Alfian, Nurul; Heryadi, Ahmad Yudi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study analyzes the application of management accounting to support the growth and sustainability of MSMEs in the Pamekasan Food Colony. A descriptive qualitative method was used, with data collection through in-depth interviews, participant observation, and document analysis. Findings indicate that the application of management accounting remains limited due to low accounting literacy and unstructured financial record keeping. Management functions such as planning, organizing, directing, and controlling are mostly carried out informally. Government support through training, provision of facilities, and digital mentoring are important factors in strengthening MSME businesses. Other factors supporting sustainability include access to capital, product innovation, compliance with local regulations, and the use of social media for marketing. This study emphasizes the need to improve accounting literacy and digitize recording systems to strengthen the competitiveness of MSMEs in the digital economy era.